Eksistensi Model Kurikulum Pendidikan Anak Usia Dini - Fauzi Fahmi; Rahmi Wardah Ningsih (STAI Auliaurrasyidin Tembilahan, 2021)
Curriculum of Early Childhood Education is a set of plans about early childhood learning goals ranging from 0 to 6 years old which intend to develop children's potential optimally. Poor of teacher attention and unfortunate infrastructure lead to unappropriate children’s potential development. The objectives of this study are to: 1) describe the form of a curriculum development model for early childhood education, and 2) describe the implementation of the curriculum model for early childhood education. This research uses a literature study method that relies on bibliographical sources from books and articles in scientific journals related to the subject matter. The results of this study indicate that: 1) the curriculum development model for early childhood education can be changed by adding, reducing and improving the curriculum regularly, 2) curriculum models for early childhood education include: a) High / Scope curriculum, b) Creative curriculum, and c) The Vygotsky Curriculum. d) The Waldorf Curriculum.